The birth of Europe the history of Christian church from John Chrysostom to the conversion of Russia (AD 398-999) : church history unfolded, through the stories that are the inheritance of all believers - Churchill, Leigh (Carlisle, UK Paternoster, 2001)
Includes bibliographical references and index.
Keywords: Church history -- middle ages -- Europe